Determinants of benchmarking adoption - Lee, Yean Pin (2004)
Stiff competition and technology advancement have driven many companies for continuous improvement in their processes, products and services. Benchmarking, as one of the simple yet effective techniques, is vital for performance improvement in many areas. Nevertheless, benchmarking adoption is found lacking in the manufacturing sectors in Penang.